An Alternative Genesis for Pisolites and Channel Iron Deposits in Western Australia (The Australasian Institute of Mining and Metallurgy, 2009)
The current genesis of pisolites and channel iron deposits (CID) has been defined in a way that presents CID as unique in the world. The published material on detrital pisolites mostly details the West Australian CID; most other global occurrences of iron-rich pisolites would seem to have an in situ genesis. An alternate theory for the origin of the Hamersley CID is suggested, involving an older greensand protore derived from volcanic ash and deposited on a glaciated Hamersley surface. This paper presents the author's observations, sampling and mapping after several years study and exploration for pisolites and CID in WA and in some locations overseas. It is not what one would call scientifically complete, and possibly asks more questions than it answers, but it is presented as a point for discussion.